The Scenario of National Thermal Power Corporation Pre and post Disinvestments - A paired t test analysis - Gupta, Mukesh Kumar; Acharjee, Gokul; Pandit, Abhijit; Kumar, Harendra (The journal of contemporary issues in business and government, 2023)
According to the global restructuring trend, the reform and restructuring process in the Indian electrical industry has been ongoing since 1992. This paper describes the current state of the Indian power industry and highlights the government's recent restructuring efforts and policies. Several essential parts of the reform agenda have been executed with differing degrees of success in various Indian states. A reorganization concept for UPPCL is offered. If necessary, this model may be implemented at the national level with appropriate revisions. Many developing and transition nations have implemented market- oriented reforms in their electric power sectors since about 1990. Despite extensive use of a uniform policy model, reform procedures and results have often fallen short of expectations. This study examines common elements of non-OECD electrical reform and reassesses reform programs and underlying assumptions based on a comprehensive literature analysis and case studies in Asia, Africa, Latin America, and Eastern Europe. In contrast to the sector-focused policy aims of deregulation in OECD nations, non- OECD changes are shaped by national fiscal crises, macroeconomic reforms, and lobbying by international lenders. It also emphasizes reform's reliance on recruiting foreign money and, as a result, its susceptibility to fluctuating international financial circumstances. A wide variety of non-OECD reform experiences show that a restricted emphasis on finance and cost recovery, when implemented rigidly, typically leads in poor outcomes. According to the study, strengthening reform would need a larger range of goals, such as service supply, public benefits, effective regulation, and social/political legitimacy. Reforms must, above all, be founded on realistic evaluations of national needs and capacities.